Bio-oxidation of a low grade chalcopyrite ore by mixed culture of acidophilic bacteria - Baba, A A; Ezekafor, E E; Adekola, F A; Ahmed, R N; Panda, S (Journal of Ecobiotechnology, 2012)
A study on the extent of biooxidation of a low grade Chalcopyrite ore using a mixed acidophilic bacterial consortium predominantly of the Acidithiobacillus ferrooxidans strain has been carried out.Â The influence of additive and pH on the bio-oxidation of the ore has been examined. The results of the investigations showed that bio-oxidation was enhanced by the addition of nutrient broth at lower pH. The enhancement in biooxidation of a chalcopyrite ore was 54% and 19% with and without addition of broth in 10 days incubation time, respectively. The study showed that at a lower pH (â‰¤ 4.0), the biooxidation of the ore was higher in presence of broth. Consequently, in presence of nutrient broth, the concentration of Fe and Cu leached were 1200 mg/L and 350 mg/L; and without nutrient broth yielded 580 mg/L and 220 mg/L, respectively within 10 days of incubation and decreases afterwards.